Ефективність виробництва і реалізації торгівельного обладнання на прикладі УП ТОВ "Wiko-Украина" - Макаренко, Анастасія Борисівна; Бєлімова, О. О. (НТУ "ХПІ", 2010)
Приведены результаты исследований эффективности производства и реализации торгового оборудования на примере УП ТОО "Wiko-Украина". Рассчитаны экономический эффект и экономическая эффективность продажи партии витрин холодильных, кассовых боксов и стеллажей на рынок России на условиях Inco-terms – FCA.

The efficiency results of production and selling of trading equipment by UP Ltd "Wiko-Ukraine" are given. The economic effect and economic efficiency of realization of party refrigerated showcases, cash boxes and racks to the Russian market according to the Incoterms – FCA are calculated.
Keywords: торгівельний сектор; експортна діяльність; ринок; підприємства; торгівельне обладнання